Courtesy stigma from the perspectives of elementary school educators in South Korea. (December 2020) - Cho, Minhae; Yun, Heejung; Haight, Wendy
Highlights: Individuals supporting children with disabilities at school experienced courtesy stigmatization. Courtesy stigmatization impacts psychological functioning of individuals around children with disabilities. Vulnerabilities for courtesy stigmatization arise in the unique Korean sociocultural context. Experience of courtesy stigmatization vary across social roles in supporting children with disabilities. Abstract: Stigmatization is a culturally widespread educational and social justice issue. This qualitative study examines Korean educators' perspectives of courtesy stigmatization based on their own firsthand experiences of courtesy stigmatization, as well as their observations of the social, emotional and behavioral reactions of close associates of children with disabilities. We conducted semi-structured, individual interviews with 43 Korean educators. Analytic induction was used to interpret participants' perspectives on issues and effects of courtesy stigma at school settings. Educators' discussions revealed a number of general characteristics of Korean culture that create vulnerabilities for courtesy stigmatization experienced by associates with children with disabilities including presumed poor parenting for misbehaviors of children with disabilities, social hierarchy in interpersonal relationships, and strong societal values on academic success. Educators also described how the sociocultural context creates unique experiences of stigmatization to special education teachers, family members, and peers of children with disabilities. Educators further discussed how courtesy stigmatization impedes the psychological and social functioning of children with disabilities. The perspectives of educators in Korea can be used to develop stigma sensitive policies and practice to better support children with disabilities.